Penerapan MEDIA GAMBAR BERBASIS POP UP BOOK DALAM MENGEMBANGKAN KEMAMPUAN MENGENAL HURUF PADA ANAK USIA DINI - Ismawati; Muh. Rusdi T; Ahmad Afiif (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
One of the media that can be used in developing the ability to recognize letters is image media based on the pop-up book. This study aims to determine the role of the pop-up book-based image media in developing the ability to recognize letters in early childhood. The type of research used is library research. Sources of data used are secondary data sources, namely in the form of a collection of scientific papers (journals, theses, and articles) and books that are relevant to the research variables to be studied. Data analysis techniques use content analysis. The results showed that pop-up book-based image media played a role in developing the ability to recognize letters in children. From the results of data exposure analysis, it was found that the pop-up book-based image media can develop children's ability to recognize letters from one another and recognize the characteristics, sounds of letters, and the shapes of the letters. The development of the ability to recognize letters occurs because of the completeness of the pop-up book-based image media features in the form of images that look like the original because they are three-dimensional, dance forms of media and various colors, each word represents each letter and various themes. This research implies that pop-up book-based image media plays a role in improving the ability to recognize letters for early childhood. Increasing the ability to recognize letters through the pop-up book-based image media cannot be separated from the advantages possessed by pop-up book media.